2002
DOI: 10.1152/ajpregu.00455.2001
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen phosphorylase and pyruvate dehydrogenase transformation in white muscle of trout during high-intensity exercise

Abstract: We examined the regulation of glycogen phosphorylase (Phos) and pyruvate dehydrogenase (PDH) in white muscle of rainbow trout during a continuous bout of high-intensity exercise that led to exhaustion in 52 s. The first 10 s of exercise were supported by creatine phosphate hydrolysis and glycolytic flux from an elevated glycogenolytic flux and yielded a total ATP turnover of 3.7 micromol x g wet tissue(-1) x s(-1). The high glycolytic flux was achieved by a large transformation of Phos into its active form. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…ATP content did not differ between velocities. Depletion of ATP is closely linked to fatigue (McFarlane & McDonald 2002, Richards et al 2002, which indicates that, irrespective of current velocity, the fish in the present study did not deplete their energy reserves, nor were they close to fatigue. In addition, lactate levels were not elevated in the fast velocity treatment, which may have been expected if there was anaerobic swimming activity.…”
Section: Metabolic Effects and Blood Chemistrymentioning
confidence: 56%
“…ATP content did not differ between velocities. Depletion of ATP is closely linked to fatigue (McFarlane & McDonald 2002, Richards et al 2002, which indicates that, irrespective of current velocity, the fish in the present study did not deplete their energy reserves, nor were they close to fatigue. In addition, lactate levels were not elevated in the fast velocity treatment, which may have been expected if there was anaerobic swimming activity.…”
Section: Metabolic Effects and Blood Chemistrymentioning
confidence: 56%
“…4B) that act in tandem to maintain a low and steady lactate concentration in the circulation (<1mmoll -1 ; Fig.1B). Work by Richards et al has shown that the pyruvate dehydrogenase complex probably plays a key regulatory role in sustaining lactate production in normoxic fish (Richards et al, 2002). Rainbow trout support higher baseline turnover rates for lactate (~15molkg ) (Haman et al, 1997b;Shanghavi and Weber, 1999;Weber and Shanghavi, 2000), and the same pattern has been observed in humans (Stanley et al, 1985;Weber et al, 1990).…”
Section: Lactate Production and Hypoxiamentioning
confidence: 79%
“…The immediate energy supply for contraction in the fast muscle comes from the hydrolysis of phosphocreatine and is supplemented by anaerobic glycogenolysis during prolonged high-speed swimming, resulting in the accumulation of lactic acid (Hochachka, 1985;Richards et al, 2002). The rate of radial diffusion of a substance is proportional to the reciprocal of the square root of the relative molecular mass, and is much greater for relatively large molecules such as lactate than oxygen (Kinsey and Moerland, 2002).…”
Section: Scaling Of Maximum Fibre Diametermentioning
confidence: 99%